Student’s Self-Assessment Regarding the Clinical Skills in Forensic Medicine - Taufik Suryadi; Kulsum Kulsum (Budapest International Research and Critics University, 2020)
In the learning process in forensic medicine clinical rotation, a measurable and standardized evaluation system is needed. The preliminary survey is undertaken to assess the ability of the student in clinical skills in rotation of forensic medicine. This survey was carry out in the Faculty of Medicine, Universitas Syiah Kuala, Banda Aceh, Indonesia. The instrument used in this study was a questionnaire. Data was analyzed is done manually. As many as 81 medical students were included in the survey (20 male and 61 female). The average student score is based on survey 3.40, while the average academic value was given by the lecturer is 3.49. The survey was invalid with sensitivity 0.519, and specificity 0.593 (value<0,6). In this survey, found the validity of student self-assessment not valid in determining the ability of clinical skills, it is influenced by several factors of objectivity and subjectivity of assessment both in terms of students and lecturers. In general, student’s clinical skills in accordance with the achievement of competency in clinical rotation of forensic medicine.